Short Communication: The clay nanoparticle impregnation for increasing the strength and quality of sengon (Paraserianthes falcataria) and white meranti (Shorea bracteolata) timber - TAMAN ALEX; BUDI WINARNI; IRAWAN WIJAYA KUSUMA; ENOS TANGKE ARUNG; EDY BUDIARSO (Nusantara Bioscience, 2017)
Alex T, Winarni B, Kusuma IW, Arung ET, Budiarso E. 2017. Short Communication: The clay nanoparticle impregnation for increasing the strength and quality of sengon (Paraserianthes falcataria) and white meranti (Shorea bracteolata) timber. Nusantara Bioscience 9: 107-110. The clay nanoparticle impregnation for increasing the strength and quality of sengon (Paraserianthes falcataria) and white meranti (Shorea bracteolata) timber. The clay nanoparticles as a fine particle material dissolved in water was impregnated into the sengon and white meranti timber in order to improve its strength properties. Impregnation is the process of inserting the material dissolved in specific water or liquid in the timber using vacuum tube and air pressure. Materials used in this study were clay nanoparticles and the sample test of sengon (P. falcataria) and white meranti (S.bracteolata) timbers with a size of 2 cm x 2 cm x 40 cm. A total of 30 samples for each type of dried timber were impregnated using clay nanoparticles with a pressure of 60 psi for 2 hours. The results showed that impregnation with clay nanoparticles at concentrations of 5% gave the retention value of sengon and white meranti timber of 22.73 kg.m3 and 24.89 kg.m3, respectively. Wood strength is indicated by the voltage value at the boundary proportion (SPL), modulus of rupture (MOR) and modulus of elasticity (MOE). sengon timber shows the value of SPL, MOR, MOE by 296.57 kg.cm2, 376.36 kg.cm2, and 38027.663 kg.cm2, while the white meranti timber had the value of SPL, MOR, MOE as follows: 623, 32 kg.cm2, 729.69 kg.cm2 and 160.187 kg.cm2. The strength of sengon timber was increased from class V (very low) to class IV (low), whereas white meranti was increased from class IV (low) into class II (strong).